Gretchen Waller, barrel racer (1967)
Barrel racer Gretchen Waller competes at the Poly Royal Rodeo, 1967 It is believed that Gretchen Waller was not a Cal Poly student, but rather a student from Arizona State, who came to compete at the Cal Poly Rodeo during Poly Royal, 1967.